Surveillance programs for detection and characterization of emergent pathogens and antimicrobial resistance: results from the Division of Infectious Diseases, UNIFESP - Arnaldo L. Colombo (Anais da Academia Brasileira de Ciências, 2009)
Several epidemiological changes have occurred in the pattern of nosocomial and community acquired infectious diseases during the past 25 years. Social and demographic changes possibly related to this phenomenon include a rapid population growth, the increase in urban migration and movement across international borders by tourists and immigrants, alterations in the habitats of animals and arthropods that transmit disease, as well as the raise of patients with impaired host defense abilities. Continuous surveillance programs of emergent pathogens and antimicrobial resistance are warranted for detecting in real time new pathogens, as well as to characterize molecular mechanisms of resistance. In order to become more effective, surveillance programs of emergent pathogens should be organized as a multicenter laboratory network connected to the main public and private infection control centers. Microbiological data should be integrated to guide therapy, adapting therapy to local ecology and resistance patterns. This paper presents an overview of data generated by the Division of Infectious Diseases, Federal University of São Paulo, along with its participation in different surveillance programs of nosocomial and community acquired infectious diseases. Várias alterações epidemiológicas ocorreram no perfil das doenças infecciosas hospitalares e comunitárias nos últimos 25 anos. Mudanças sociais e demográficas possivelmente relacionadas com esse fenômeno incluem o rápido crescimento populacional, o aumento da migração urbana e deslocamento através de fronteiras internacionais por turistas e imigrantes, alterações nos habitats de animais e artrópodes que transmitem doença assim como o aumento no número de pacientes com deficiências nas respostas de defesa. Os programas contínuos de vigilância de patógenos emergentes e resistência antimicrobiana são necessários para a detecção em tempo real de novos patógenos assim como para caracterizar mecanismos moleculares de resistência. Para serem mais efetivos, os programasde vigilância dos patógenos emergentes devem ser organizados em uma rede de laboratórios multicêntricos ligados aos principais centros de controle de infecções, públicos e privados. Os dados microbiológicos devem ser integrados a guias terapêuticos adaptando práticas terapêuticas à ecologia local eaos padrões de resistência. O artigo apresenta uma revisão dos dados gerados pela Disciplina de Infectologia, Universidade Federal de São Paulo, contemplando sua participação nos diferentes programas de vigilância de doenças infecciosas hospitalares e adquiridas na comunidade.